James Watt: a trajetória que levou ao desenvolvimento da máquina a vapor vista por seus biógrafos e homens de ciências - Tavares, Luiz Alberto (2008)
The aim of this paper is to discuss the Scotch James Watt s work in the improvement of the steam engine. This research considered studies of historians from the Nineteenth-Century contemporary with him and historians from the Twentieth-Century who saw him in a more critical way. We also consider the relationship between Watt and his partners at the University of Glasgow and at the Lunar Society, as well as his partnership with Thomas Boulton for the commercialization of the steam engine. Another point of this work is the building of his image as the main inventor of the steam engine